Rapid prototyping of 3D printed PLC kits for education - Karim M.H.A.; Khairudin A.R.M.; Azlan M.A.F.M.; Zian N.M.; Muliady N.A.I.; Anwar N.A.F.F.; Karim M.H.A. (American Institute of Physics Inc., 2023)
3D Printed Trainer for Rapid Prototyping instruction sets is easily attainable, yet, the current model is less practical as it requires a large space to operate and also time consuming to be manufactured. While we are fiercely fighting the Covid-19 pandemic, the Malaysian government has initiated Movement Control Order, and this makes a more portable and lightweight design becomes more demanding. The new design is more cost effective and has been improved from the previous designs. Therefore, this paper presents the improvement of a Programmable Logic Controller (PLC) 3D Printed Trainer kit for Rapid Prototyping for Industrial Automation course. This kit is just 250mm x 150mm x 170mm in size and weight less than 5kg which does not only make it mobile and easy to carry but it also suits to be used for teaching and learning application. 2021 Author(s).